The Borana wells. An introductory description and preliminary information of selected Borana wells in the Southern Rangelands Development Project area - Donaldson, T.J. (International Livestock Centre for Africa, 1983)
Presents preliminary results of a Well Utilization Survey conducted in the Southern Rangelands Development Project area, locating well groups & their specific wells, identifying certain limiting aspects to their use & providing brief descriptions of selected Borana wells. Includes well dimension estimates & maps of these dry season wells, & specifies problems of each well group.